Spatial and temporal patterns in microcystin toxins in Lake of the Woods surface waters. (2nd October 2017) - Zastepa, Arthur; Watson, Susan B.; Kling, Hedy; Kotak, Brian
ABSTRACT: Zastepa A, Watson SB, Kling H, Kotak B. 2017. Spatial and temporal patterns in microcystin toxins in Lake of the Woods surface waters. Lake Reserve Manag. 33:433–443. Lake of the Woods (LOW) is a complex system, with limited exchange between its multiple basins and strong spatial variance in physicochemical conditions and susceptibility to cyanobacterial blooms (cHABs). Nutrient input from tributaries has contributed to a highly productive southern basin with widespread cHABs, which are also present in some northern sub-basins. To date, there is no systematic lake-wide assessment of spatial and temporal patterns of microcystins (MCs) in relation to cyanobacterial taxa along physicochemical gradients. To achieve this, surface waters were sampled June to September in 2006, 2008–2010, and 2014–2015 offshore, inshore, and along developed shorelines. Offshore MC measured by ELISA and PPIA was consistently low despite high chlorophyll- a (Chl- a ) (e.g. 0.7 µg MC-LR equivalents/L; 126 µg/L Chl- a ), with only two cases exceeding the 20 µg MC-LR equivalents/L World Health Organization recreational guideline. LC-MS/MS analysis of MC congeners (2014–2015) showed MC-LR dominating, with MC-LA also present. A strong positive correlation of MC with NO3 ( P < 0.005) was observed but not with other nutrients, water transparency, or mixing. The toxicity of phytoplankton biomass was positively correlated with dissolved P and inversely with particulate N:P ( P < 0.02, P < 0.001 respectively), suggesting lower toxicity under P-deficiency. Shorelines contained much higher MC concentrations with more than 25% above 20 µg MC-LR equivalents/L in 2006 and 2009 (maximum ∼ 600 µg MC-LR equivalents/L). Several potential producers of MCs were suspected, including Dolichospermum and Microcystis . Cyanobacteria identified in LOW are known elsewhere as producers of other toxins including neurotoxins, but these have not yet been assessed in LOW.